N-Acetylcysteine Use in Non-Acetaminophen-Induced Acute Liver Failure. (July 2016) - McPheeters, Chelsey M.; VanArsdale, Vanessa M.; Weant, Kyle A.
Abstract : This article will review the available evidence related to the management of non-acetaminophen induced acute liver failure with N -acetylcysteine. Randomized controlled trials and a meta-analysis were included in this review. The efficacy of N -acetylcysteine in the treatment of acute liver failure from causes other than acetaminophen toxicity was evaluated. The efficacy of N -acetylcysteine in non-acetaminophen-induced acute liver failure is limited to specific patient populations. Patients classified as Coma Grade I or II are more likely to benefit from the use of this agent. The use of N -acetylcysteine is associated with improved transplant-free survival, not overall survival, in adults. N -Acetylcysteine does not improve the overall survival of patients with non-acetaminophen-induced acute liver failure but may be beneficial in those patients with Coma Grades I–II. Liver transplantation remains the only definitive therapy in advanced disease.